Impact of interactivity of electronic word of mouth systems and website quality on customer e-loyalty - Mubbsher Munawar Khan; Hammad Bin Azam Hashmi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
In this study, we aim to identify the impact of interactivity of electronic word of mouth (EWOM) systems on customer e-loyalty based on Interactivity Theory. In electronic market place, consumers now interact with e-retailers and other consumers with the help of EWOM systems. We have also tried to identify the impact of website quality on customer e-loyalty. An empirical data of 400 respondents is collected through questionnaires in the city of Lahore, Pakistan. Structural Equation Modeling (SEM) is employed to analyze the key relationships. Findings show that interactivity of EWOM systems has a positive influence on customer e-loyalty. If this interaction is properly managed, it can increase the customer e-loyalty. Findings also show that website quality has a positive influence on customer e-loyalty. In the context of electronic commerce, EWOM systems are of uprising concern. These findings could be of help to the electronic commerce companies in raising their customers' e-loyalty by appropriately managing their EWOM systems.
Keywords: 330; electronic word of mouth (EWOM); decision support; e-loyalty; interactivity of EWOM systems; website quality